The state of agricultural extension services in Ethiopia and their contribution to agricultural productivity - Berhane, Guush; Ragasa, Catherine; Abate, Gashaw T.; Assefa, Thomas (International Food Policy Research Institute, 2018)
We document the state of the extension system in Ethiopia and review the empirical evidence on the links between the key extension services provided, adoption of modern inputs, and agricultural productivity. In particular, we take stock of the provision of agricultural extension services, synthesize the evidence on the performance of the system, and suggest ways that it might contribute to accelerating agricultural growth and poverty reduction in the years ahead.